Ophthalmologists' and patients' perspectives on treatments for diabetic retinopathy and maculopathy in Vietnam: a descriptive qualitative study. Issue 7 (7th July 2022) - Curran, Katie; Lohfeld, Lynne; Congdon, Nathan; Peto, Tunde; Hoang, Tung Thanh; Nguyen, Hue Thi; Nguyen, Quan Nhu; Nguyen, Van Thu; Dardis, Catherine; Tran, Hoang; Tran, Hoang Huy; Vu, Anh Tuan; et al.
Abstract : Introduction: Globally, diabetic retinopathy (DR) is the leading cause of blindness in working-aged adults. Early detection and treatment of DR is essential for preventing sight loss. Services must be available, accessible and acceptable to patients if we are to ensure they seek such care. Objectives: To understand patients' knowledge and attitudes towards laser versus antivascular endothelial growth factor (VEGF) injections to treat DR in Vietnam, and to identify factors Vietnamese ophthalmologists consider when making treatment decisions. Methods: This is a descriptive qualitative study based on semi-structured interviews with 18 patients (12 from Ho Chi Minh City and 6 from Hanoi) plus individual interviews with 24 ophthalmologists working in eye clinics in these cities. Thematic analysis was used to analyse the data. Results: In total, 10/24 (41.7%) ophthalmologists were female, and their median age was 41 years (range 29–69 years). The median age of patients was 56.5 years (range 28–72 years), and 7/18 (38.9%) were female. Briefly, factors that influence DR treatment decisions for ophthalmologists are medical considerations (ie, severity of disease, benefits and risks), availability (ie, treatment and resources) and patient-related factors (ie, costs and adherence). Patient's perceived barriers and facilitators to treatments were based on patient and family related factors (ie, treatment and transportation costs) and previous treatment experiences (ie, positive and negative). Recommendations by all participants included ensuring that both laser and anti-VEGF injections are widely available across the country and controlling costs for patients and the healthcare system. Conclusions: Reducing DR treatment costs, optimising treatments options, and expanding the network of clinics offering treatment outside metropolitan areas were the main issues raised by participants. These findings can help inform policy changes in Vietnam and may be generalisable to other low-resource settings.